Case Report: Respiratory Management With a 47-Day ECMO Support for a Critical Patient With COVID-19 - Xu, Wen; Tan, Ruoming; Huang, Jie; Qin, Shuai; Wu, Jing; Qiu, Yuzhen; Xie, Simin; Xu, Yan; Du, Ying; Li, Feng; Li, Bailing; Li, Yingchuan; et al. (Frontiers in Medicine, 2021)
This paper reports a complete case of severe ARDS caused by COVID-19, who presented with rapid deterioration of oxygenation during hospitalization despite escalating high-flow nasal cannulation to invasive mechanical ventilation. After inefficacy with lung-protective ventilation, PEEP titration, prone position, we administered ECMO as a salvage respiratory support with ultra-protective ventilation for 47 days and finally discharged the patient home with a good quality of life after 76 days of hospitalization. The purpose of this paper is to provide a clinical reference for the management of ECMO and respiratory strategy of critical patients with COVID-19-related ARDS.